2014
DOI: 10.4314/wsa.v41i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Coping with drought: the experience of water sensitive urban design (WSUD) in the George Municipality

Abstract: This study investigated the extent of Water Sensitive Urban Design (WSUD) activities in the George Municipality in the Western Cape Province, South Africa, and its impact on water consumption. The WSUD approach aims to influence design and planning from the moment rainwater is captured in dams, to when it is treated, and reticulated to consumers, and extending to the point of wastewater re-use, as well as stormwater use. The study identified 8 WSUD sub-activities stemming from 4 main WSUD activities, implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The review found just one article that discusses the use of NBS for reduction of drought risk. Lottering et al, (2015) discussed the effectiveness of NBS on reduction of water consumption in suburb areas.…”
Section: (1) Effectiveness Of a Single/individual Nbs Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The review found just one article that discusses the use of NBS for reduction of drought risk. Lottering et al, (2015) discussed the effectiveness of NBS on reduction of water consumption in suburb areas.…”
Section: (1) Effectiveness Of a Single/individual Nbs Sitementioning
confidence: 99%
“…-Australia (Lottering et al, 2015;Mouritz, 1996;Whelans consultants et al, 1994) Sustainable Urban Drainage Systems (SuDS)…”
Section: Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This offers a unique opportunity to implement innovative solutions based on integrated urban water management [98]. There are some initial attempts of Sponge City in South Africa [115][116][117]. However, the successful experience in some places cannot be applied to other places.…”
Section: Challenges Standing Aheadmentioning
confidence: 99%
“…The sponge city initiative was inspired by low impact developments (LID) elsewhere in the world that would be scaled and transferred into the Chinese urban context. These existing developments include LID in the US [2], water sensitive urban design (WSUD) in Australia [3], sustainable urban drainage systems (SUDS) in the UK [4], and integrated urban water management systems in Denmark and Sweden [5] [6]. For example, in Malmö, different storm-water collection networks as well as large-scale open storm-water handling implementations are already present in forms such as ponds, wetlands, swales, canals, detention lakes, and green roofs [5].…”
Section: Introductionmentioning
confidence: 99%